Farmer Perspectives On Livelihoods Within Grape Community In South Tangerang City - Lorenta In Haryanto (State University of Gorontalo, 2022)
Grape vines are cultivated in South Tangerang City, not only by farmers, but also by members of a grape community. This research aimed 1) to describe the characteristics of grape farmers, 2) to show the perspective of grapes farmer, and 3) to identify problems and expectations in carrying out grape vines cultivation in South Tangerang City. Data collected through the interview, observation and sharing questionnaires. The number of samples was determined proportionally to 68 grape farmers, who are members of the grape community in South Tangerang City (KAT). The results showed that grape farmers tended to be knowledgeable and educated, specified by productive age (20-40 years old) with less experiences in grape cultivation. Based on the perspective analysis, farmers were attracted to grape farming not because of the influence of farm-families background, but because of hobbies and self interest in grapes cultivation. Farmers considered that agriculture was a noble and a matter of pride. The most common problems facing grape farmers were the insufficient land, inadequate agricultural funding base, and formulating the ideal growing media. The results of the expectation analysis proved that training program was the most desired assistance for farmers, especially effort to increase grape productivity.